DESAIN GELANGGANG OLAHRAGA LAPANGAN FUTSAL DENGAN KONSEP BAJA MASUK DESA - Muhammad Zakaria Umar (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2022)
The building structure should be effective. The IWF steel profile structure is more effective for use in the futsal field sports arena. The futsal building is a wide span building. On the other hand, the euphoria of futsal is not only in big cities, but also in rural areas such as in Pangan Jaya Village, Lainea District, South Konawe Regency. This study was aimed at designing a futsal field sports arena with an IWF steel profile structure in Pangan Jaya Village. This study uses architectural (design) methods with a qualitative approach. The data sources in this study consist of primary data sources and secondary data sources. Data collection techniques were carried out by means of observation, interviews, and documentation. The data analysis technique was carried out by collecting data, reducing data, presenting data, and summarizing data. Based on the results of this research design, it is concluded that the futsal field sports arena is designed with the concept of Steel Entering the Village (SEV) as follows: First, the author wants to socialize steel materials in rural communities; Second, steel structures are quite effective for use in buildings; Third, steel poles using IWF iron and H-beam; Fourth, the middle structure consists of steel poles, steel beams, and reinforcing cables; Fifth, the upper frame structure system uses a portal frame.